Insulin sensitivity in individuals with burnout is associated with physical activity level – a study using oral glucose tolerance test - Lennartsson, Anna-Karin; Jonsdottir, Ingibjörg H.; Jansson, Per-Anders; Sjörs Dahlman, Anna (Frontiers in Psychiatry, 2026)
AimsBurnout is caused by long term psychosocial stress and has, besides the fatigue and mental health burden, been associated with increased risk of adverse physical health, such as type 2 diabetes. Physical activity seems to be a protective factor against burnout and its negative health consequences. This study aims to investigate the glucose and insulin levels related to physical activity level in individuals with stress related burnout, by assessing these metabolic markers in response to a standard oral glucose tolerance test (OGTT).MethodsAltogether, 38 individuals with burnout (13 men and 25 women) in the age 24–55 were included in the study. The burnout cases were divided into three groups based on self-reported physical activity level.ResultsThe burnout cases who reported that they were sedentary exhibited significantly higher insulin levels during the OGTT compared to burnout cases reporting that they were physically active to any degree. This relationship was independent of severity of symptoms of burnout and depression.ConclusionsThe observed higher insulin levels in the sedentary burnout cases indicate an increased diabetes risk in these individuals and point at an important reason for physical activity being included in the treatment regimen for this patient group.